Urinary cytokines as markers of latent inflammation in children with chronic pyelonephritis and anorectal malformations. Issue 3 (June 2016) - Morozov, Dmitry; Morozova, Olga; Budnik, Ivan; Pervouchine, Dmitri; Pimenova, Evgeniya; Zakharova, Natalya
Summary: Introduction: Anorectal malformations (ARMs) comprise a range of defects in the development of the lowest portion of the intestinal tract that are often associated with anomalies of the urinary tract. We hypothesize that ARMs may specifically predispose the patients to prolonged urinary tract infection (UTI) and transition from a state of active (clinically apparent) inflammation to a state of latent inflammation following antibiotic treatment. Yet diagnosis of latent inflammation in the urinary tract is problematic. Objective: The aim was to investigate the urinary levels of proinflammatory (IL-1β, IL-6, IL-8, and MCP-1), anti-inflammatory (IL-10), and proangiogenic (VEGF) cytokines in the clinical course of chronic pyelonephritis (CP) as potential biomarkers of latent inflammation in the urinary tract in children with ARM. Patients and methods: A total of 34 children (age range 4–120 months) with CP in the active phase of inflammation were divided into two groups: CP with ARM group included 20 patients and CP without ARM group included 14 patients. The control group included 20 healthy children similar by age and gender. Urine samples were collected at the time of enrollment, 5–7 days after institution of antibiotic treatment, and 1.5 months after enrollment. Cytokine concentrations were measured by ELISA. Results: Upon enrollment, we detected increased urinary levels of IL-10 and MCP-1 and normal levels of IL-1β, IL-6, IL-8, and VEGF in CP with ARM patients as well as normal levels of all of these cytokines in CP without ARM patients. After 5–7 days of antibiotic treatment, despite significant clinical and laboratory improvement observed in both patient groups, we documented a prominent increase in the urinary concentrations of all measured cytokines indicating ongoing inflammation in the urinary tract. Following 1.5 months of enrollment, in CP without ARM patients, IL-8 and MCP-1 were increased, IL-1, IL-6, and VEGF were close to control, and IL-10 was below the control level, indicating partial resolution of the inflammatory process. In contrast, in CP with ARM patients, IL-1β, IL-6, IL-8, MCP-1, and VEGF were increased suggesting persistent inflammation in the urinary tract (Table). Conclusion: Based on the urinary cytokine profile, we conclude that presence of ARM may be associated with transition from active to latent inflammation in the urinary tract after antibiotic treatment for UTI. Follow-up monitoring of the urinary cytokines may provide a better assessment of inflammatory activity in the urinary tract in children with combined urological and anorectal pathologies. Table Urinary cytokine concentrations in healthy controls and chronic pyelonephritis patients 1.5 months after enrollment. Cytokine Control CP with ARM CP without ARM Median (IQR) Median (IQR) p vs. control Median (IQR) p vs. control p vs. CP with ARM IL-1β 3.7 (1.2–7.4) 33.2 (19.4–55.9) <0.001 4.0 (3.2–5.7) 0.375 <0.001 IL-6 2.4 (1.5–3.5) 52.5 (29.3–109.1) <0.001 4.9 (4.2–7.4) 0.218 0.047 IL-8 6.1 (4.9–9.5) 389.7 (371.4–400.4) <0.001 236.3 (197.6–326.9) 0.017 0.196 IL-10 6.4 (5.5–9.7) 6.9 (3.5–18.1) 0.375 1.7 (1.2–3.1) 0.011 0.007 VEGF 166 (142–238) 733 (597–792) <0.001 312 (218–384) 0.255 0.041 MCP-1 122 (107–154) 425 (354–509) <0.001 367 (329–392) 0.002 0.375 Note. Concentrations are given in pg/mL. P values were calculated using the Kruskal–Wallis test followed by the post hoc Dann test and adjusted for multiple comparisons. CP = chronic pyelonephritis; ARM = anorectal malformation; IQR = interquartile range.